TRANSLANGUAGING IN ENGLISH-NEPALI BILINGUAL SPACE IN UNIVERSITY-LEVEL ENGLISH READING INSTRUCTION - Bal Ram Adhikari; Prem Prasad Poudel; Xiangyu Li (TEFLIN Journal, 2024)
Framed within pedagogical translanguaging, this qualitative case study explored university teachers’ translanguaging practices in the bilingual space in English reading instruction. Data were gathered through class observations and semi-structured interviews with four teachers instructing English reading courses in the Bachelor of Education (B.Ed.) program at a university in Nepal. Analysis reveals teachers’ heteroglossic awareness that inspired them to embed the translanguaging strategy in reading instruction despite the university's monolingual orientation. Perceived as the irreducible fabric of bi/multilingual classrooms, English-Nepali translanguaging was integrated into reading lessons for different purposes, such as, to orient students to texts, enhance students’ access to text content and language, and optimize reader-text interaction and collaborative meaning construction. The study highlights how teachers can leverage students’ bi/multilingual resources to compensate for and complement their emergent meaning-making and meaning-sharing processes in English reading. These findings imply that idealized monolingual instructional practices commonly promoted through conventional approaches and methods are to be revisited and the role of learners’ prior and emergent linguistic repertoires is to be repositioned in EFL contexts. The study sees the need for further exploration of the translanguaging praxis in EFL contexts to institutionally validate the deployment of bi/multilingual resources for learning enhancement.